O percurso do conceito de fim de análise de Freud a Lacan - Martins, Ana Carolina Borges Leão (2010)
Our research aims at following the formulations for the concept of end of analysis beginning with Freud, going through the post-Freudians, and reaching the teaching contributions from Lacan. To this end we divided our path methodologically in three distinct segments: 1. the pathway for defining the concept of end of analysis as propounded by Freud; 2. the investigation of the concept of cure and end of analysis in the theoretical productions of Freud’s contemporaries and post-Freudians; 3. the reassessment of therapeutic perspectives and the concept of end of analysis as contributed by Jacques Lacan. In the first moment, we were shown how the inception of the concept of death drive in 1920 contributed to the final break-up between end of analysis and therapeutic intents. We were also able to discuss treatment guidelines as propounded by Freud, the hurdles impeding the cure and the adoption of end of analysis, and the technical proposition for analysis construction, an artificial solution advanced by Freud to counter the difficulties with analytical treatment. In the second part, we investigated solutions as propounded by post-Freudian analysts to the problem of the economics of compulsion. We set out from the hypothesis according to which the analytical movement did not accept easily the contributions from the concept of death drive, rather opting for interpreting them as a lessening of therapeutic results. Within this view, two obstacles impeded the analytical treatment turning it into a never-ending task: in 1930, character was an obstacle to cure because of its close relation to the obscure ways of drive satisfaction; in 1950, the analyst’s self blurred the good development of transference, appearing as an inconvenient waste from the end sought by didactical and therapeutic analyses. In the last part of our work, the constitution of topic in its imaginary configuration, having its source on Lacan’s contributions, conferred intelligibility to the standstill reached by post-Freudian analysts. Under the aegis of a configuration shaped by imaginary values we demonstrated the disastrous results from the attempt to elide the unconscious discourse from the analytical treatment, and we pointed to a Lacanian proposal of resuming field references for speech and language. At the end of our pathway, we accompanied Lacan’s critical appraisal of the model for IPA formation and his solution to the problem, namely, the pass procedure to deal with the limits of analytical formation and end of analysis. As a conclusion, we could evaluate how our work throws a light upon issues referring to the analyst’s formation and how it contributes to psychoanalysis transmission.